Final report : FRGS 16-054-0553. Exploring the utilization of geographic information system to study the root causes of obesity in Kuantan, Pahang - Mohd Abu Bakar, Wan Azdie (2020)
Childhood obesity is now becoming a major public health concern in Malaysia. National prevalence of childhood obesity kept increasing year after year. This study aims to explore the prevalence and the severity of childhood obesity and to investigate its relationship with certain community level characteristics. Nowadays, obesity has been associated with food insecurity. Food insecurity is always linked to undernutrition but recently the focus of food insecurity begins to also include its relationship with obesity. Therefore, the aim of this study was to identify the prevalence and the severity of food insecurity and how it is associated with childhood obesity. Proportionate random sampling was carried out and a total of 1160 primary and secondary school children participated in this study with informed consent from their parents. The study area was in the district of Kuantan, Pahang. The respondents’ weight and height were measured and these data was converted and compared against BMI-for-age z-score (BMIAZ) and Height-for-age z-score (HAZ). One set of questionnaire was used to obtain the sociodemographic data and food security status information. The validated food security questionnaire known as Radimer/Cornell Hunger and Food Security Instrument (Malay version) was used to discriminate the severity of household food insecurity into mild, moderate and severe. All the data was linked to Geographical Information System (GIS) where the distribution map of nutritional status and household food security status of the children were generated. The study found that the prevalence of childhood obesity and overweight were high at 15.3 % (n=197) and 13.9 % (n=179) respectively. The prevalence of food insecurity also very concerning where 76% (n=981) of them experienced food insecurity while only 24% (n=309) food secured. Therefore, this study showed that childhood obesity and food insecurity were co-existing in Kuantan, Pahang and their prevalence are very alarming.